Investigation on the Air Filter with Industrial Ducting System - Nasri, Muhammad Aiman; Sies, Mohamad Farid (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Air filter is one of the element in Local Exhaust Ventilation (LEV) system that have been widely used in industry to encounter air pollution. The objective of this study is to investigate the velocity distribution and pressure drop in air filter by using computational fluid dynamic (CFD) software. A simulation study was carried out to obtain the velocity and pressure distribution in air filter. This study was performed with three types of filters that is fibrous filter, pleated filter and High Efficiency Particulate Air (HEPA) filter. The analysis of velocity and pressure behavior in air filter is from the inlet to the outlet of the system. The CFD software used in this study is Ansys Fluent Fluid Flow. It can be observed that the pressure drop and the performance of tested filter is influenced by the permeability of the filter. From the result obtained, HEPA filter is the most preferable because it has the least value of pressure drop and the velocity distribution on the system is more balance. Furthermore, high permeability filter is more efficient compared to low permeability filter when it operates in the system.